Đánh giá xác suất nguy hiểm động đất Bà Rịa - Vũng Tàu - Sơn, Lê Tử (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Probabilistic seismic hazard assessment for Ba Ria - Vung Tau Based on recent researches on tectonic and seismic activities in the southern part of Central Vietnam, seismic hazard assessment for Ba Ria - Vung Tau is done by probabilistic approach. The results show that, at the returned period of 475 years, the PGA on rock site range from 0.03 to 0.05 g in the whole province. At the coastal lines and in Vung Tau city, the PGA are higher than other sites and reach 0.048g - 0.051g. In the Con Dao island PGA is 0.0183g (lowest in the province).